The Effect of Job Insecurity and Workload on Turnover Intention and Organizational Commitment as Mediating Variables (A Study of Employees at TVRI Maluku Station) - Agusthina Risambessy (Sean Institute, 2026)
Human resources must be managed effectively in order to contribute positively to the organization’s progress. This study aims to examine and analyze the effects of job insecurity and workload on turnover intention; to examine and analyze the effects of job insecurity and workload on organizational commitment; and to examine and analyze the indirect effects of job insecurity and workload on turnover intention and organizational commitment. The study sample at TVRI Maluku Station consisted of 67 participants, selected using a saturation sampling technique, and analyzed using path analysis. The results of the study demonstrate that job insecurity influences turnover intention, and that workload has a significant effect on turnover intention and organizational commitment. Employee job insecurity has a significant direct negative effect on organizational commitment. Employee workload has a significant negative effect on organizational commitment. Organizational commitment has a significant positive effect on turnover intention. Job insecurity has a significant negative effect on turnover intention through organizational commitment. Workload has a significant negative effect on turnover intention through organizational commitment. It is recommended that future researchers explore the variable of job satisfaction by expanding the scope of their research.